Too much finance or statistical illusion: A comment - Jean Louis Arcand; Enrico Berkes; Ugo Panizza (Graduate Institute of International and Development Studies, 2015)
A recent policy brief from the Peterson Institute suggests that the "Too Much Finance" result may be an artifact of spurious attribution of causality. While more works needs do be done to understand the links between finance and growth and explore the drivers of possible non-monotonicities, this note shows that the too much finance result is robust.
Keywords: 330